Analysis of six prophages in Lactococcus lactis IL1403: different genetic structure of temperate and virulent phage populations - Chopin, Alain (Oxford University Press, 2001)
We report the genetic organisation of six prophages present in the genome of Lactococcus lactis IL1403. The three larger prophages (36–42 kb), belong to the already described P335 group of temperate phages, whereas the three smaller ones (13–15 kb) are most probably satellites relying on helper phage(s) for multiplication. These data give a new insight into the genetic structure of lactococcal phage populations. P335 temperate phages have variable genomes, sharing homology over only 10–33% of their length. In contrast, virulent phages have highly similar genomes sharing homology over >90% of their length. Further analysis of genetic structure in all known groups of phages active on other bacterial hosts such as Escherichia coli, Bacillus subtilis, Mycobacterium and Streptococcus thermophilus confirmed the existence of two types of genetic structure related to the phage way of life. This might reflect different intensities of horizontal DNA exchange: low among purely virulent phages and high among temperate phages and their lytic homologues. We suggest that the constraints on genetic exchange among purely virulent phages reflect their optimal genetic organisation, adapted to a more specialised and extreme form of parasitism than temperate/lytic phages.